2017
DOI: 10.1080/03007995.2017.1367275
|View full text |Cite
|
Sign up to set email alerts
|

Long-term persistence with single-pill, fixed-dose combination therapy versus two pills of amlodipine and perindopril for hypertension: Australian experience

Abstract: Use of a single-pill, fixed-dose combination in hypertension is associated with superior persistence and reduced mortality compared with use of two pills, suggesting a higher priority for the use of fixed-dose combinations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 10 publications
0
18
0
6
Order By: Relevance
“…Patients initiated with a SPC had a significantly higher proportion of total follow-up days covered with medications and a lower frequency of the primary outcome [ 27 ]. Recently also, it has been shown, in a large group of Australian hypertensive patients, that treatment with SPCs resulted in a lower mortality compared to patients taking the same antihypertensive agents in separate pills [ 28 ]. We found that, in accordance with the 2013 ESH-ESC guidelines [ 1 ], many GPs consider switching from free combinations to SPCs, with the hope of improving therapeutic compliance and blood pressure control.…”
Section: Discussionmentioning
confidence: 99%
“…Patients initiated with a SPC had a significantly higher proportion of total follow-up days covered with medications and a lower frequency of the primary outcome [ 27 ]. Recently also, it has been shown, in a large group of Australian hypertensive patients, that treatment with SPCs resulted in a lower mortality compared to patients taking the same antihypertensive agents in separate pills [ 28 ]. We found that, in accordance with the 2013 ESH-ESC guidelines [ 1 ], many GPs consider switching from free combinations to SPCs, with the hope of improving therapeutic compliance and blood pressure control.…”
Section: Discussionmentioning
confidence: 99%
“…All 29 studies reported on adherence and/or persistence in patients taking SPC therapy for hypertension. Four studies were RCTs (14%) [35,37,38,46]; the remainder (n ¼ 25; 86%) were observational studies [14,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]36,[39][40][41][42][43][44][45]47] (Table S3, http://links.lww.com/HJH/B268). Sample sizes varied considerably, from n ¼ 75 to n ¼ 79 958 for SPC therapy and n ¼ 73 to n ¼ 383 269 for free-dose combination therapy.…”
Section: Study Populations and Antihypertensive Therapy Prescribedmentioning
confidence: 99%
“…Furthermore, nonadherence was also confirmed as an important contributor to the higher hospitalization rate and health care cost 20 . Currently, FDC is widely used in several chronic diseases such as hypertension, DM, and pulmonary tuberculosis to simplify treatment regimens, improving medication adherence and clinical outcomes 10,12,21‐24 . In our previous study, compared to the free combination of CCB/ARB, the FDC of amlodipine/valsartan improves MACE‐free survival, medication compliance, hospitalization rates, and also decreases total health care costs 12 .…”
Section: Discussionmentioning
confidence: 89%
“…Previously, several studies have suggested that, in hypertensive patients, fixed‐dose combination (FDC) is more effective to control blood pressure than free‐equivalent combination (FEC) or monotherapy 9‐11 . Better medication compliance with FDC regimens may significantly reduce the major adverse cardiovascular events (MACE) and health care costs, 12,13 which was also recommended by the current major guidelines 14,15 .…”
Section: Introductionmentioning
confidence: 99%